Groundwater quality issues and management in Ramganga Sub-Basin - Natarajan, Rajmohan; Amarasinghe, Upali A. (Springer, 2016)
Groundwater quality receives increasing attention in water management in India. The purpose of this paper is to highlight the emerging issues of groundwater quality in the Ramganga Sub-Basin (RSB), a tributary joining the Ganga River from the northern plains, which extends over 30,839 Sq. km and covers 15 districts in both Uttarakhand and Uttar Pradesh. The groundwater in most of the districts of the RSB has high concentration of nitrate, iron, salinity and fluoride, which exceed the standards prescribed for drinking water by the Bureau of Indian Standards (BIS) and World Health Organization (WHO). Arsenic contamination in groundwater is an emerging issue in few groundwater development blocks. Moreover, groundwater with substantial hardness, high sulfate, and high manganese is emerging issue in some districts. Additionally, shallow aquifers have high concentration of ions. In the RSB, the quality of groundwater, especially in the shallow aquifers, is influenced by the contamination of poor quality surface water, due mainly to poor sanitation, improper disposable of domestic sewage water, manures and irrigation return flows. To reduce deterioration of water quality further, the RSB requires proper sanitation facilities, efficient usage of agrochemicals, as well as an awareness program of water-related disease.